Sensitization Pattern of Inhalant Allergens in Children With Asthma Who Are Living Different Altitudes in Turkey - Õzkaya, E.; Söǧüt, A.; Küçükkoç, M.; Eres, M.; Acemoglu, H.; Yüksel, H.; Murat, N. (Springer New York LLC barbara.b.bertram@gsk.com, 2015)
Variability in children’s allergic sensitization has been detected not only among different countries but also among cities within the same nation but yet different climatic areas. The aim of this study was to investigate the sensitization pattern of asthmatic children who lived in different altitude areas: the two largest Turkish cities, Istanbul (sea level) and Erzurum (high altitude). Five hundred and twelve asthmatic children (6–15 years old) from Istanbul (western Turkey, at sea level) and 609 from Erzurum (eastern Turkey, at an altitude of 1800 m) were included in the study. All participants underwent skin testing with common inhalant allergens, spirometry, total IgE level, and clinical examination. The positive sensitization ratio to aeroallergens in children with asthma living at sea level was statistically higher than that in children living in the high altitude group [p = 0.001, OR (odds ratio) 4.9 (confidence interval (CI) 3.67–6.459)]. However, pollen sensitization in asthmatic children living in high altitudes was significantly higher than that in children living at sea level [p = 0.00, OR 2.6 (CI 1.79–3.87)]. Children with asthma who live at high altitudes are characterized by higher pollen but lower mite sensitization rates than those living at sea level in Turkey. Different climatic conditions and altitudes may affect aeroallergen sensitization in children with asthma. © 2015, ISB.
Keywords: Aeroallergen; Altitude; Asthma; Children; Humidity; Mite; Pollination